Artificial muscle fiber based on liquid crystal elastomer as well as preparation method and application of artificial muscle fiber

By combining spring-like conductive fibers and liquid crystal elastomers, the mechanical strength of the artificial muscle fibers of the liquid crystal elastomers is improved, the problem of insufficient electric heat drive performance is solved, and the effect of rapid response and high driving volume is achieved. It is suitable for flexible electronics and soft robots. field.

CN119162829AActive Publication Date: 2024-12-20NANJING DRUM TOWER HOSPITAL
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411532410.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2024-12-20
Estimated Expiration
2044-10-30

AI Technical Summary

Technical Problem

The existing liquid crystal elastomer artificial muscle fibers have insufficient mechanical strength in electric thermal driving, which affects their fast and precise driving performance.

Method used

Spring-like conductive fibers are combined with liquid crystal elastomer oligomers, and mechanical strength is enhanced through the support framework of the conductive fibers, and multi-domain conductive liquid crystal elastomer fibers are prepared through mechanical stretching and cross-linking reactions to achieve rapid response and high driving. quantity.

Benefits of technology

Without affecting the driving performance, the mechanical strength of the fiber is significantly improved, fast and accurate electric heating drive is achieved, with high sensitivity and high output force, and is suitable for flexible electronics and soft robots.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119162829A_ABST
    Figure CN119162829A_ABST
Patent Text Reader

Abstract

The invention discloses an electro-thermal driven artificial muscle fiber based on a liquid crystal elastomer, which improves the overall mechanical strength of the fiber without influencing the driving performance, can realize rapid and accurate driving, and has the characteristic of rapid response. The electro-thermal driven liquid crystal elastomer artificial muscle has high sensitivity, high driving quantity and high output force, can achieve 60% of maximum driving quantity within 0.3 s, has large driving force on the premise of meeting large driving quantity, and has wide research prospects in the fields of flexible electronics, soft robots and rehabilitation medicine. The preparation method is simple in preparation process and easy to operate, and large-scale preparation can be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of artificial muscles, and in particular relates to artificial muscle fibers based on liquid crystal elastomers and a preparation method and application thereof. Background Art

[0002] In the field of materials science and intelligent robotics, the rapid development of flexible electronics has spawned a series of innovative materials with unprecedented performance, providing new impetus for the development of soft robots. With the deepening of research, a new type of composite fiber material has emerged, which shows excellent characteristics in human-machine interaction, deformation recovery and mechanical properties. This composite fiber material is widely regarded as the key driving unit in soft robots, namely artificial muscle fibers. They can not only provide powerful power output, but also work in a low-noise environment, giving robots unprecedented freedom and flexibility. In addition, artificial muscle fibers can be combined with flexible electronics technology to achieve self-perception and feedback, which is crucial for building autonomous and dexterous soft robots.

[0003] Artificial muscle fibers have extremely high performance requirements, including fast actuation response, large actuation strain and stress, excellent flexibility and controllability. These requirements have driven the research and development of liquid crystal elastomer fibers (LCE). LCE fibers are composed of oriented liquid crystal polymers and have a high thermal shrinkage effect along the molecular chain direction. Therefore, they have high deformation ability, excellent mechanical properties and reversible deformation characteristics, making them ideal materials for manufacturing artificial muscles. Although LCE fibers show great potential in the manufacture of artificial muscles, the actuation mechanisms proposed in existing studies usually rely on external factors such as environmental heating, light, magnetism or humidity, which limits the controllability of the robotic system. Electrothermal technology has particular application potential in artificial muscle fibers for soft robots. Artificial muscle fibers driven by electrothermal technology can achieve fast response and precise control, which is crucial to improving the performance of robots.

[0004] The advantages of electrothermally driven liquid crystal elastomer (LCE) artificial muscles are their fast response, high power output, and excellent controllability. This driving method can directly convert electrical energy into thermal energy, and use the thermal expansion or phase change of the material to achieve rapid contraction and relaxation of artificial muscles. Compared with traditional methods such as photothermal, magnetic thermal, and direct heating, electrothermal drive avoids dependence on external light sources or magnetic fields, and provides more stable and controllable power output. Electrothermally driven LCE artificial muscles also have the characteristics of simple structure and easy integration. By adjusting the size and direction of the current, the degree of contraction and movement mode of the muscle can be precisely controlled to achieve high controllability and flexibility. In addition, the electrothermal drive has a fast response speed and can achieve material deformation at the millisecond level, which is particularly important for application scenarios that require fast response. In addition, electrothermally driven LCE artificial muscles also have good environmental adaptability. They can work stably under different environmental conditions, including extreme temperature and humidity conditions, which provides more possibilities for the application of artificial muscles.

[0005] When exploring the electrothermal drive method of liquid crystal elastomers (LCE), researchers have developed a variety of strategies to achieve efficient and controllable driving performance. For example, by combining liquid metals (such as mercury and gallium) with LCE, the electrothermal effect of liquid metal can be used to drive the deformation of LCE. The advantage of this method is that the fluidity of liquid metal will not limit the deformation of LCE, but at the same time, the presence of liquid metal may reduce the mechanical strength of LCE. Embedding serpentine metal wires in LCE is also a common electrothermal drive method. The metal wires generate heat when current passes through, causing the deformation of LCE. However, the addition of metal wires may affect the uniformity of LCE, thereby reducing its overall driving performance. Composite of LCE with nanocarbon materials: Nanocarbon materials such as graphene and carbon nanotubes are used for electrothermal drive of LCE due to their excellent electrical conductivity and thermal properties. The composite of these materials can improve the electrothermal conversion efficiency, but the conductivity is not as good as that of metals, which may affect the driving performance. Summary of the invention

[0006] Purpose of the invention: The purpose of the present invention is to provide an artificial muscle fiber based on liquid crystal elastomer and electrically driven by heat, which can improve the overall mechanical strength of the fiber without affecting its driving performance, and can achieve fast and precise driving.

[0007] Technical solution: The artificial muscle fiber based on liquid crystal elastomer described in the present invention is prepared from spring-shaped conductive fibers and liquid crystal elastomer oligomers.

[0008] Preferably, the conductive fiber is one of metal wire, nylon fiber, carbon fiber, conductive polymer, shape memory alloy wire or carbon nanotube wire.

[0009] The present invention also provides a method for preparing artificial muscle fibers based on liquid crystal elastomers, comprising the following steps: 1) Preparation of spring-shaped conductive fibers; 2) Preparation of liquid crystal elastomer oligomers; 3) Preparation of artificial muscle fibers based on liquid crystal elastomers: The liquid crystal elastomer oligomer solution obtained in step 2) is perfused into a tetrafluoroethylene tube containing the conductive fibers prepared in step 1); after the cross-linking reaction, the tetrafluoroethylene tube is peeled off to obtain a multi-domain conductive liquid crystal elastomer fiber; after removing the solvent, the multi-domain conductive liquid crystal elastomer fiber is stretched and secondary cross-linked to obtain the final artificial muscle fibers based on liquid crystal elastomers.

[0010] Preferably, the inner diameter of the tetrafluoroethylene tube is 1-6 mm.

[0011] Preferably, the stretching step is to mechanically stretch the multi-domain conductive liquid crystal elastomer fibers by 3 times using a mechanical stretching method.

[0012] Preferably, the preparation method of the spring-shaped conductive fiber is as follows: the conductive fiber is wound on a stainless steel core shaft, and after high-temperature heating and annealing, the core shaft is taken out to obtain a spring-shaped conductive fiber that is tightly wound.

[0013] Preferably, the diameter of the conductive fiber is 0.1-1.0 mm, the diameter of the stainless steel mandrel is 0.6-3.0 mm, the temperature of the high-temperature heating annealing is 120-180° C., and the time is 1.5-3 hours.

[0014] Preferably, the liquid crystal elastomer oligomer is prepared by the aza-Michael addition method, and the specific process is as follows: the liquid crystal monomer, chain extender, cross-linker and photoinitiator are dissolved in a solvent, stirred and dissolved at 40-80°C to prepare a uniform solution, and then a catalyst is added and stirred continuously to obtain a liquid crystal elastomer oligomer solution.

[0015] Preferably, the liquid crystal monomer is any one or two of 1,4-di[4-(3-acryloxypropoxy)benzoyl]-2-toluene or 2-methyl-1,4-phenylenebis(4-((6-(acryloxy)hexyl)oxy)benzoate); the chain extender is any one or more of 3,6-dioxa-1,8-octanedithiol, ethylene glycol bis(3-mercaptopropionate), 1,4-butanediol bis(thioglycolate), ethylene glycol bis(thioglycolate), bis(2-mercaptoethyl) ether, 1,3-propanedithiol, 1,6-hexanedithiol, and 1,10-decanedithiol.

[0016] Preferably, the solvent is selected from any one or more of dichloromethane, ethyl acetate, toluene or acetone; the crosslinking agent is pentaerythritol tetrakis(3-mercaptopropionate), the photoinitiator is 2,2-dimethoxy-2-phenylacetophenone, and the catalyst is di-n-propylamine.

[0017] The present invention also provides the application of artificial muscle fibers based on liquid crystal elastomers in the preparation of flexible electronics and soft robots.

[0018] Beneficial effects:

[0019] The electrothermally driven artificial muscle fiber based on liquid crystal elastomer provided by the present invention first constructs a conductive spring, and then uses a template method to coat the liquid crystal elastomer, wherein the conductive spring can play a role in supporting the skeleton and improving the mechanical output, and when the liquid crystal elastomer is deformed, the spring will not hinder its deformation effect; the present invention can improve the overall mechanical strength of the fiber without affecting its driving performance, can achieve fast and precise driving, and has the characteristics of fast response. The electrothermally driven liquid crystal elastomer artificial muscle has high sensitivity, high driving amount and high output force, and can achieve 60% of the maximum driving amount within 0.3s. It has a large driving force while meeting the large driving amount, so that it has broad research prospects in the fields of flexible electronics, soft robots and rehabilitation medicine. The preparation method of the present invention has a simple and easy-to-operate preparation process, and can achieve large-scale preparation. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is a flow chart of the preparation of the spring-shaped conductive fiber of the present invention.

[0021] Figure 2 It is a flow chart of the preparation of artificial muscle fibers of the present invention.

[0022] Figure 3 This is an optical photograph of the artificial muscle fiber of the present invention.

[0023] Figure 4 It is the driving amount of the artificial muscle fiber of the present invention at different voltages when the frequency is 0.1 Hz (duty cycle is 5%).

[0024] Figure 5 It is the driving amount of the artificial muscle fiber of the present invention at different voltages when the frequency is 0.1 Hz (duty cycle is 10%).

[0025] Figure 6 This is a comparison of the driving performance of conductive liquid crystal elastomer fibers prepared from conductive nylon fibers of different diameters. DETAILED DESCRIPTION

[0026] In order to deepen the understanding of the present invention, the present invention will be further described in detail below in conjunction with embodiments and drawings. The embodiments are only used to explain the present invention and do not constitute a limitation on the protection scope of the present invention. Example 1

[0027] 1) Preparation of conductive spring: Conductive nylon fiber with a diameter of 0.1 mm is used as the conductive fiber, and it is evenly wound on a stainless steel mandrel with a diameter of 0.6 mm ( Figure 1 A), fix the two ends and anneal in an oven at 120℃ for 3 hours, take out the mandrel, and obtain a densely wound conductive nylon spring ( Figure 1 B), the conductive spring has excellent elasticity and can be stretched by more than 500% ( Figure 1 C).

[0028] 2) Preparation of liquid crystal elastomer oligomer: Liquid crystal elastomer oligomer was prepared by aza-Michael addition method, and the specific process was as follows: 2.0 mmol of liquid crystal monomer (RM257, 1,4-di[4-(3-acryloxypropoxy)benzoyl]-2-toluene), 1.73 mmol of chain extender (EDDET, 3,6-dioxa-1,8-octanedithiol), 0.173 mmol of cross-linker (PETMP, pentaerythritol tetrakis(3-mercaptopropionic acid) ester), 0.04 mmol of photoinitiator (IG-651, 2,2-dimethoxy-2-phenylacetophenone) were dissolved in 1.2 mL of dichloromethane, and the mixture was stirred and dissolved at 50°C for 20 minutes to prepare a uniform solution. Finally, 0.04 mmol of catalyst (DPA, di-n-propylamine) was added and stirred for 1 minute to obtain a liquid crystal elastomer oligomer solution (transparent liquid) for use.

[0029] 3) Preparation of conductive liquid crystal elastomer fibers: The conductive nylon spring prepared in (1) was placed in a tetrafluoroethylene tube with an inner diameter of 1.0 mm ( Figure 2 A and Figure 2 B), the liquid crystal elastomer oligomer solution obtained in (2) is injected into the tetrafluoroethylene tube containing the conductive nylon spring using a syringe ( Figure 2 C). After preliminary cross-linking for 24 hours in a light-proof state, the tetrafluoroethylene tube was peeled off to obtain a multi-domain conductive liquid crystal elastomer fiber ( Figure 2 D), and placed it in an oven at 80 degrees Celsius to remove excess solvent for 24 hours. The multi-domain conductive liquid crystal elastomer fibers were mechanically stretched 3 times ( Figure 2 E), and then secondary cross-linking is performed under ultraviolet light for 15 minutes to obtain uniaxially oriented conductive liquid crystal elastomer fibers, that is, the final conductive liquid crystal elastomer fibers are obtained for standby use ( Figure 2 F).

[0030] Figure 3This is an optical photograph of the conductive liquid crystal elastomer fiber in this embodiment, and the fiber diameter is 0.7 micrometers. When the conductive liquid crystal elastomer is mechanically stretched, the liquid crystal unit is transformed from the nematic phase to the isotropic phase, resulting in macroscopic deformation and excellent driving performance. WAXS is used to characterize its internal orientation. Example 2

[0031] 1) Preparation of conductive spring: Carbon fiber with a diameter of 0.1 mm was used as the conductive fiber. It was first twisted to a certain twist (not twisted to a spiral state), and then evenly wound on a stainless steel mandrel with a diameter of 1.0 mm. After fixing both ends, it was annealed in an oven at 150°C for 2 hours. The mandrel was taken out to obtain a densely wound conductive carbon fiber spring.

[0032] 2) Same as step (2) of Example 1.

[0033] 3) Preparation of conductive liquid crystal elastomer fibers: The conductive carbon fiber spring prepared in (1) is placed in a tetrafluoroethylene tube with an inner diameter of 1.0 mm, and the liquid crystal elastomer oligomer solution obtained in (2) is injected into the tetrafluoroethylene tube containing the conductive carbon fiber spring using a syringe. After preliminary cross-linking for 24 hours in a light-proof state, the tetrafluoroethylene tube is peeled off to obtain a multi-domain conductive liquid crystal elastomer fiber, which is placed in a 60-degree Celsius oven to remove excess solvent for 24 hours. The multi-domain conductive liquid crystal elastomer fiber is mechanically stretched 3 times by mechanical stretching, and secondary cross-linked for 15 minutes under ultraviolet light to obtain the final conductive liquid crystal elastomer fiber for use. Example 3

[0034] 1) Preparation of conductive spring: Conductive nylon fiber with a diameter of 0.1 mm is used as the conductive fiber, and it is evenly wound on a stainless steel mandrel with a diameter of 0.6 mm ( Figure 1 A), fix the two ends and anneal in an oven at 140℃ for 2.5 hours, take out the mandrel, and obtain a densely wound conductive nylon spring ( Figure 1 B), the conductive spring has excellent elasticity and can be stretched by more than 500% ( Figure 1 C).

[0035] 2) Preparation of liquid crystal elastomer oligomer: Liquid crystal elastomer oligomer was prepared by aza-Michael addition method, and the specific process was as follows: 2.0 mmol of liquid crystal monomer (RM257, 1,4-di[4-(3-acryloxypropoxy)benzoyl]-2-toluene), 1.73 mmol of chain extender (DDT, 1,10-decanedithiol), 0.173 mmol of cross-linker (PETMP, pentaerythritol tetrakis(3-mercaptopropionic acid) ester), 0.04 mmol of photoinitiator (IG-651, 2,2-dimethoxy-2-phenylacetophenone) were dissolved in 1.2 mL of ethyl acetate, and the mixture was stirred and dissolved at 50°C for 20 minutes to obtain a uniform solution. Finally, 0.04 mmol of catalyst (DPA, di-n-propylamine) was added and stirred for 1 minute to obtain a liquid crystal elastomer oligomer solution (transparent liquid) for use.

[0036] 3) Same as step (3) of Example 1. Example 4

[0037] 1) Same as step (1) of Example 1.

[0038] 2) Preparation of liquid crystal elastomer oligomer: Liquid crystal elastomer oligomer was prepared by aza-Michael addition method, and the specific process was as follows: 2.0 mmol of liquid crystal monomer (RM257, 1,4-di[4-(3-acryloxypropoxy)benzoyl]-2-toluene), 1.73 mmol of chain extender (HDT, 1,6-hexanedithiol), 0.173 mmol of cross-linker (PETMP, pentaerythritol tetrakis(3-mercaptopropionic acid) ester), 0.04 mmol of photoinitiator (IG-651, 2,2-dimethoxy-2-phenylacetophenone) were dissolved in 1.2 mL of toluene, and the mixture was stirred and dissolved at 50°C for 20 minutes to obtain a uniform solution. Finally, 0.04 mmol of catalyst (DPA, di-n-propylamine) was added and stirred for 1 minute to obtain a liquid crystal elastomer oligomer solution (transparent liquid) for use.

[0039] 3) Same as step (3) of Example 1. Example 5

[0040] The driving performance test was carried out using the conductive liquid crystal elastomer fiber prepared in Example 1. The driving performance of the conductive liquid crystal elastomer under different voltages was tested at a frequency of 0.1 Hz (duty cycle of 5%). Figure 4 At a voltage of 1.0 V / cm, the maximum driving amount can reach 65%. At the same time, as the voltage increases, the driving amount increases, indicating that the conductive liquid crystal elastomer fiber has the ability to work with a large driving amount. Example 6

[0041] The driving performance test was carried out using the conductive liquid crystal elastomer fiber prepared in Example 1. The driving performance of the conductive liquid crystal elastomer under different voltages was tested at a frequency of 0.1 Hz (duty cycle of 10%). Figure 5 As shown. At a voltage of 1.0 V / cm, the maximum driving amount can reach 70%. At the same time, as the voltage increases, the driving amount increases, indicating that the conductive liquid crystal elastomer fiber has the ability to work with a large driving amount. Compared with Example 2, the duty cycle increases, the power-on time is extended, and its driving amount increases. Example 7

[0042] (1) Preparation of conductive spring: Conductive nylon fiber with a diameter of 0.2 mm was used as the conductive fiber. It was evenly wound on a stainless steel mandrel with a diameter of 0.6 mm. After fixing both ends, it was annealed in an oven at 120°C for 3 hours. The mandrel was taken out to obtain a densely wound conductive nylon spring.

[0043] (2) Same as step (2) of Example 1.

[0044] (3) Preparation of conductive liquid crystal elastomer fibers: The conductive nylon spring prepared in (1) was placed in a tetrafluoroethylene tube with an inner diameter of 1.2 mm. The remaining steps were the same as step (3) of Example 1. Example 8

[0045] (1) Preparation of conductive spring: Conductive nylon fiber with a diameter of 0.3 mm was used as the conductive fiber. It was evenly wound on a stainless steel mandrel with a diameter of 0.6 mm. After fixing both ends, it was annealed in an oven at 120°C for 3 hours. The mandrel was taken out to obtain a densely wound conductive nylon spring.

[0046] (2) Same as step (2) of Example 1.

[0047] (3) Preparation of conductive liquid crystal elastomer fiber: The conductive nylon spring prepared in (1) was placed in a tetrafluoroethylene tube with an inner diameter of 1.4 mm. The remaining steps were the same as step (3) of Example 1. Example 9

[0048] (1) Preparation of conductive spring: Conductive nylon fiber with a diameter of 0.4 mm was used as the conductive fiber. It was evenly wound on a stainless steel mandrel with a diameter of 0.6 mm. After fixing both ends, it was annealed in an oven at 150°C for 2 hours. The mandrel was taken out to obtain a densely wound conductive nylon spring.

[0049] (2) Same as step (2) of Example 1.

[0050] (3) Preparation of conductive liquid crystal elastomer fiber: The conductive nylon spring prepared in (1) was placed in a tetrafluoroethylene tube with an inner diameter of 1.6 mm. The remaining steps were the same as step (3) of Example 1. Example 10

[0051] (1) Preparation of conductive spring: Conductive nylon fiber with a diameter of 0.5 mm was used as the conductive fiber. It was evenly wound on a stainless steel mandrel with a diameter of 0.6 mm. After fixing both ends, it was annealed in an oven at 120°C for 3 hours. The mandrel was taken out to obtain a densely wound conductive nylon spring.

[0052] (2) Same as step (2) of Example 1.

[0053] (3) Preparation of conductive liquid crystal elastomer fibers: The conductive nylon spring prepared in (1) was placed in a tetrafluoroethylene tube with an inner diameter of 1.8 mm. The remaining steps were the same as step (3) of Example 1.

[0054] The driving performance characteristics (driving amount and contraction force) of conductive liquid crystal elastomer fibers prepared from conductive nylon fibers with different diameters are compared, such as Figure 6 As shown. Figure 6 It can be seen that the conductive liquid crystal elastomer fiber greatly improves the driving force while meeting a large driving amount (>30%).

[0055] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. An artificial muscle fiber based on liquid crystal elastomer, characterized in that: The invention is prepared from spring-shaped conductive fibers and liquid crystal elastomer oligomers; the conductive fibers are selected from metal wires, nylon fibers, carbon fibers, conductive polymers, shape memory alloy wires or carbon nanotube wires.

2. The method for preparing artificial muscle fibers based on liquid crystal elastomer according to claim 1, characterized in that: The following steps are involved: 1) Preparation of spring-shaped conductive fibers; 2) Preparation of liquid crystal elastomer oligomers; 3) Preparation of artificial muscle fibers based on liquid crystal elastomers: The liquid crystal elastomer oligomer solution obtained in step 2) is perfused into a tetrafluoroethylene tube containing the conductive fibers prepared in step 1); after the cross-linking reaction, the tetrafluoroethylene tube is peeled off to obtain a multi-domain conductive liquid crystal elastomer fiber; after removing the solvent, the multi-domain conductive liquid crystal elastomer fiber is stretched and secondary cross-linked to obtain the final artificial muscle fibers based on liquid crystal elastomers.

3. The preparation method according to claim 2, characterized in that: The inner diameter of the tetrafluoroethylene tube is 1-6 mm.

4. The preparation method according to claim 2, characterized in that: The stretching step is to mechanically stretch the multi-domain conductive liquid crystal elastomer fibers by 3 times using a mechanical stretching method.

5. The preparation method according to claim 2, characterized in that: The preparation method of the spring-shaped conductive fiber is as follows: the conductive fiber is wound on a stainless steel core shaft, and after high-temperature heating and annealing, the core shaft is taken out to obtain a spring-shaped conductive fiber that is tightly wound.

6. The preparation method according to any one of claim 5, characterized in that: The diameter of the conductive fiber is 0.1-1.0 mm, the diameter of the stainless steel core shaft is 0.6-3.0 mm, the temperature of the high-temperature heating annealing is 120-180° C., and the time is 1.5-3 hours.

7. The preparation method according to claim 2, characterized in that: The liquid crystal elastomer oligomer is prepared by the aza-Michael addition method, and the specific process is as follows: liquid crystal monomer, chain extender, crosslinker and photoinitiator are dissolved in a solvent, stirred and dissolved at 40-80° C. to prepare a uniform solution, and then a catalyst is added and stirred continuously to obtain a liquid crystal elastomer oligomer solution.

8. The preparation method according to claim 7, characterized in that: The liquid crystal monomer is any one or two of 1,4-di[4-(3-acryloxypropoxy)benzoyl]-2-toluene or 2-methyl-1,4-phenylenebis(4-((6-(acryloxy)hexyl)oxy)benzoate); the chain extender is any one or more of 3,6-dioxa-1,8-octanedithiol, ethylene glycol bis(3-mercaptopropionate), 1,4-butanediol bis(thioglycolate), bis(thioglycolate)ethylene glycol ester, bis(2-mercaptoethyl) ether, 1,3-propanedithiol, 1,6-hexanedithiol, and 1,10-decanedithiol.

9. The preparation method according to claim 7, characterized in that: The solvent is selected from any one or more of dichloromethane, ethyl acetate, toluene or acetone; the crosslinking agent is pentaerythritol tetrakis(3-mercaptopropionic acid) ester, the photoinitiator is 2,2-dimethoxy-2-phenylacetophenone, and the catalyst is di-n-propylamine.

10. Use of the artificial muscle fiber as described in claims 1-9 in the preparation of flexible electronics and soft robots.

Citation Information

Patent Citations

  • Sensor material based on liquid crystal elastomer and application thereof

    CN114605827A

  • High-power bidirectional-driving bionic muscle fiber and preparation method and application thereof

    CN115142267A

  • Multi-stimulus-response liquid crystal elastomer / MXene composite fiber soft driver and preparation method and application thereof

    CN116289170A

  • Spiral winding type artificial muscle and preparation method thereof

    CN117267074A

  • Preparation method of electrothermal driving type artificial muscle

    CN117961974A